THE Bahasa Inggris - Husni, Husni; Jeliana, Wa; Harun, Muhammad (English Education Journal, 2025)
The research questions of this research were: 1) whether there was any significant relationship between of motivation toward reading comprehension on SMP Negeri 3 Batuatas; 2) whether there was any significant relationship between of activeness  toward reading comprehension on SMP Negeri 3 Batuatas; and 3) whether there was any significant relationship between of motivation and activeness  toward reading comprehension on SMP Negeri 3 Batuatas. This reserach aimed to determine the relationship between of motivation toward reading comprehension, the relationship between of activeness toward reading comprehension, the relationship between of motivation and activeness toward reading comprehension on SMP Negeri 3 Batuatas. This research used a quantitative approach using the ex-post facto methods. The subject of this research were 30 respondents of the eight grade students at SMP Negeri 3 Batuatas. The data collection instruments used were questionnare and test. Data analysis in this research used data analysis techniques descriptive statistics and inferential  statistics. Based on the results of the reserach, this research had 3 conclusions. First there was no significant relationship of motivation toward reading comprehension. this conclusion  was based on statistical analysis, where the significant value was 0,471. Because the significant value was greater than α (0,05), it meant that the null hypothesis was accepted and the allternative hypothesis was rejected. Second, there was no significant relationship of activeness toward reading comprhension. This conclusion was based on statistical analysis, where the significant value was 0,797. Because the significant value was greater than α (0,05), it meant that the null hypothesis was accepted and the alternative hypothesis was rejected. Third, there was no significant relationship of motivation and activeness toward reading comprehension. this conclusion was based on statistical analysis, where the significant value was 0,733. Because the significant value was greater than α (0,05), it meant that the null hypothesis was accepted and the alternative hypothesis was rejected.